Question Number 10213 by konen last updated on 30/Jan/17

4a−b=60  2(√a)−(√b)=6  ⇒a+b=?

Answered by nume1114 last updated on 30/Jan/17

     (2(√a)−(√b))(2(√a)+(√b))=4a−b  ⇒6(2(√a)+(√b))=60  ⇒2(√a)+(√b)=10  4(√a)=(2(√a)+(√b))+(2(√a)−(√b))         =10+6=16  ⇒a=16  2(√b)=(2(√a)+(√b))−(2(√a)−(√b))         =10−6=4  ⇒b=4  ⇒a+b=16+4=20

Answered by arge last updated on 03/Feb/17

conjugada,    ((2(√(a )) −(√(b  )))/1)×((2(√(a ))+(√(b )))/(2(√(a ))+(√b)))=6    ((4a−b)/(2(√a) +(√b)))=6    4a−b=12(√a) +6(√b)........(iii)    (i) y (iii)    60=12(√a) +6(√b)  10=2(√a) +(√b)    (√(b ))=2(√(a ))−6    10=4(√a) −6  16=4(√a)  (√a) =4  a=16  b=4